Association between Blood Mercury Level and Visceral Adiposity in Adults - Park, Jong Suk (Diabetes Metab J, 2017)
BACKGROUND: Few studies have examined the association between mercury exposure and obesity. The aim of this study is to investigate the association between blood mercury concentrations and indices of obesity in adults. METHODS: A total of 200 healthy subjects, aged 30 to 64 years, who had no history of cardiovascular or malignant disease, were examined. Anthropometric and various biochemical profiles were measured. Visceral adipose tissue (VAT) was measured using dual-energy X-ray absorptiometry (DXA). RESULTS: All subjects were divided into three groups according to blood mercury concentrations. Compared with the subjects in the lowest tertile of mercury, those in the highest tertile were more likely to be male; were current alcohol drinkers and smokers; had a higher body mass index (BMI), waist circumference (WC), and VAT; had higher levels of blood pressure, fasting glucose, and insulin resistance; and consumed more fish. The blood mercury concentration was significantly associated with anthropometric parameters, showing relationships with BMI, WC, and VAT. After adjusting for multiple risk factors, the odds ratios (ORs) for high mercury concentration was significantly higher in the highest VAT tertile than in the lowest VAT tertile (OR, 2.66; 95% confidence interval, 1.05 to 6.62; P<0.05). CONCLUSION: The blood mercury concentration was significantly associated with VAT in healthy adults. Further studies are warranted to confirm our findings.